Marcadores moleculares em câncer de mama em mulheres jovens (idade < 35 anos): estudo comparativo com mulheres pós-menopausa (idade entre 50 - 65 anos) - Mara Costa Dutra (2009)
Purpose: The objective of this study was to evaluate the clinical, pathological and molecular characteristics in very young women ( 35 years) and postmenopausal (50-65 years) women with breast cancer. Methods: We selected 106 cases of breast cancer of very young women ( 35 years) and 130 cases of postmenopausal women. We evaluated clinical characteristics of patients (age at diagnosis, ethnic group, family history of breast cancer, staging, presence of distant metastases, overall and disease-free survival), pathological characteristics of tumors(tumors size, histological type and grade, axillary lymph nodes status) and expression of molecular markers (hormone receptors, HER2, p53, p63, cytokeratins 5 and 14 and EGFR) using immunohistochemistry and tissue microarray. Results: When comparing clinicopathologic variables between the age groups, younger women demonstraded greater frequency nulliparity (p = 0.03), larger tumors (p = < 0.000), higher stage disease (p = 0.01), lymph node positivity (p = 0.001) and higher grade tumors (p = 0.004). Most of young patients received chemoterapy (90,8%) and radiotherapy (85,2%) and less tamoxifen therapy (31,5%) comparing with postmenopausal women. Lower estrogen receptor positivity 49,1% (p = 0.01) and higher HER2 overexpression 28,7% (p = 0.03) were observed in young women. In 32 young patients (29.6%) and in 26 posmenopausal women (20%), the breast carcinomas were of the triple-negative phenotype (p =0,034). In 16 young women (50%) and in 10 postmenopausal women (7,7%), the tumors expressed positivity forcytokeratin 5 and/or 14, basal phenotype (p =0,064). Systemic metastases were detected in 55,3% in young women and in 39,2% in postmenopausal women. Breast cancer overall survival and disease-free survival in 5 years were, respectively, 63% and 39% for youngwomen and 75% e 67% for postmenopausal women. Conclusions: Breast cancer arising in very young women showed negatives clinicobiological characteristics and more aggressive tumors.Key words: Breast Neoplasms, Biological Markers, Prognosis, Age Groups, Survival.